Supply Chain and Marketing Performance of Arabica Coffee Commodity in Bantaeng Regency - Evi Sulfiana; Jumiati; Nurdin; Mohammad Natsir; Sri Mardiyati (International Journal of Business and Quality Research, 2025)
This study aims to analyze the supply chain and marketing performance of Arabica coffee commodities in Tompobulu District, Bantaeng Regency, South Sulawesi Province. The sampling technique used was snowball sampling, so that informants consisting of 10 Arabica coffee farmers, collectors, wholesalers, and Akar Tani Cooperative were obtained. Data analysis used quantitative and qualitative descriptive analysis. The results of this study indicate that the supply chain of Arabica coffee commodities in Tompobulu District, Bantaeng Regency consists of 4 chains, namely: (I) producers – collector trader – coffee processing industry, (II) producers – wholesalers – Akar Tani Cooperative – roastery, (III) producers – wholesalers – Akar Tani Cooperative – cafes, and (IV) producers – wholesalers – Akar Tani Cooperative – coffee shops. The marketing performance of Arabica coffee commodities was analyzed using marketing margins, farmers' share, and marketing efficiency. Marketing margin for chain I is Rp 15,000.00/kg, chain II and chain III are Rp 20,000.00, while chain IV is Rp 120,000.00/kg. Farmers share for chain I is 77.27%, chain II and chain III are 70.58%, and chain IV is 33.33%. Marketing efficiency for chain I is 4.54%, chain II and chain III are 4.7%, and chain IV is 10.27%. The marketing performance of Arabica coffee commodities in Tompobulu District, Bantaeng Regency has reached a level of efficiency and tends to be profitable for farmers.